FLORA™: Phase I development of a functional vision assessment for prosthetic vision users. (11th February 2015) - Geruschat, Duane R; Flax, Marshall; Tanna, Nilima; Bianchi, Michelle; Fisher, Andy; Goldschmidt, Mira; Fisher, Lynne; Dagnelie, Gislin; Deremeik, Jim; Smith, Audrey; Anaflous, Fatima; Dorn, Jessy
<x xml:space="preserve">Abstract</x> Background Research groups and funding agencies need a functional assessment suitable for an ultra‐low vision population to evaluate the impact of new vision‐restoration treatments. The purpose of this study was to develop a pilot assessment to capture the functional visual ability and well‐being of subjects whose vision has been partially restored with the Argus II Retinal Prosthesis System. Methods The Functional Low‐Vision Observer Rated Assessment (FLORA) pilot assessment involved a self‐report section, a list of functional visual tasks for observation of performance and a case narrative summary. Results were analysed to determine whether the interview questions and functional visual tasks were appropriate for this ultra‐low vision population and whether the ratings suffered from floor or ceiling effects. Thirty subjects with severe to profound retinitis pigmentosa (bare light perception or worse in both eyes) were enrolled in a clinical trial and implanted with the Argus II System. From this population, 26 subjects were assessed with the FLORA. Seven different evaluators administered the assessment. Results All 14 interview questions were asked. All 35 tasks for functional vision were selected for evaluation at least once, with an average of 20 subjects being evaluated for each test item. All four rating options—impossible (33 per cent), difficult (23 per cent), moderate (24 per cent) and easy (19 per cent)—were used by the evaluators. Evaluators also judged the amount of vision they observed the subjects using to complete the various tasks, with 'vision only' occurring 75 per cent on average with the System ON, and 29 per cent with the System OFF. Conclusion The first version of the FLORA was found to contain useful elements for evaluation and to avoid floor and ceiling effects. The next phase of development will be to refine the assessment and to establish reliability and validity to increase its value as an assessment tool for functional vision and well‐being.